Advances in understanding the renin-angiotensin-aldosterone system (RAAS) in blood pressure control and recent pivotal trials of RAAS blockade in heart failure and diabetic nephropathy [version 1; referees: 3 approved] - Lama Ghazi; Paul Drawz (F1000Research, 2017)
The renin-angiotensin-aldosterone system (RAAS) plays a fundamental role in the physiology of blood pressure control and the pathophysiology of hypertension (HTN) with effects on vascular tone, sodium retention, oxidative stress, fibrosis, sympathetic tone, and inflammation. Fortunately, RAAS blocking agents have been available to treat HTN since the 1970s and newer medications are being developed. In this review, we will (1) examine new anti-hypertensive medications affecting the RAAS, (2) evaluate recent studies that help provide a better understanding of which patients may be more likely to benefit from RAAS blockade, and (3) review three recent pivotal randomized trials that involve newer RAAS blocking agents and inform clinical practice.